2016
DOI: 10.4028/www.scientific.net/kem.704.343
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Deposition of PEEK/45S5 Bioactive Glass Coating on Porous Titanium Substrate: Influence of Processing Conditions and Porosity Parameters

Abstract: Commercially pure titanium (cp Ti) is typically accepted as one of the best in vitro and in vivo bone replacement biomaterial, due to its excellent balance between biomechanical and biofunctional properties. In that context, the aim of this work is to prove the hypothesis of a simultaneous solution to certain specific limitations of cpTi, which can often compromise the reliability of implants: (i) stress-shielding phenomenon, and (ii) a deficient biointerface with bone, which reduces the osseointegration. Poro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…1a). Total pore fraction, mean size and the high degree of interconnectivity ensure the bone ingrowth and the infiltration of HA [31].…”
Section: Resultsmentioning
confidence: 99%
“…1a). Total pore fraction, mean size and the high degree of interconnectivity ensure the bone ingrowth and the infiltration of HA [31].…”
Section: Resultsmentioning
confidence: 99%
“…PEEK is often employed as a mechanically robust biomaterial for orthopedic, trauma, and spinal implants . PEEK consists of an aromatic backbone molecular chain, interconnected by ketone and ether functional groups . PEEK is compatible with bioactive inorganic materials, including hydroxyapatite and bioactive glasses (BGs), which can be used either as a composite filler or as surface coating .…”
Section: Introductionmentioning
confidence: 99%
“…13,14 PEEK consists of an aromatic backbone molecular chain, interconnected by ketone and ether functional groups. [14][15][16][17] PEEK is compatible with bioactive inorganic materials, including hydroxyapatite and bioactive glasses (BGs), which can be used either as a composite filler or as surface coating. 13,18,19 In addition, PEEK/BG composite layers can act as substrate to be further coated with biodegradable composite coatings loaded with antibiotics to provide improved surfaces for antiseptic bonding to tissues.…”
Section: Introductionmentioning
confidence: 99%
“…A cold sprayed Bioglass/PEEK composite prepared by Garrido et al [143] showed an increase in wear resistance by more than 70%, higher hardness, and a lower coefficient of friction compared to pure PEEK. Coatings based on Bioglass/PEEK on porous Ti substrates resulted in higher adhesion between Bioglass/PEEK coating and Ti substrates [144].…”
Section: Polyether Ether Ketone (Peek)mentioning
confidence: 98%